Variation of Foliar Calcium and Magnesium in Six Fern Species at Different Elevations - Salazar, Laura (2021)
Several efforts have been made to understand nutrient ecology worldwide. However, Ca and Mg have received less attention, despite their function in important biological processes of plants, such us growth and photosynthesis. Few studies focus on fern nutrient ecology of foliar Ca and Mg. Moreover, none has investigated the variation of these elements along elevational gradients. Herein, we analysed if there were differences of the foliar Ca and Mg contents of six species of ferns along a tropical elevational gradient: Adiantum humile, Cyathea tortuosa, Cyclodium meniscioides, Danaea moritziana, Maxonia apiifolia, and Thelypteris biformata. We found significant differences at the interspecific and intraspecific level variation of foliar Ca and Mg contents at each elevation. In terms of the relationship between elevation and nutrient content, we found that two species showed contrasting trends of foliar Ca with elevation. Content of Ca decreased with elevation in Adiantum humile, while it increased in Maxonia apiifolia. Regarding Mg, it decreased with elevation in Adiantum humile, Thelypteris biformata and Maxonia apiifolia. However, these results were not statistically supported. An exhaustive sampling effort will provide insight on variation of foliar Ca and Mg along tropical elevation gradients and the factors influencing patterns of variation.